Neuropsychological maturity in pre-school children - Chumacero Calle, Juan Carlos (2021)
The purpose of the research was to improve neuropsychological maturity in preschool children; to achieve this; a program of strategies that reinforced the levels of neuropsychological maturity was carried out. The research had a quantitative approach, hypothetical-deductive method and quasi-experimental design; a pre-test and post-test of the Cumanin questionnaire, a valid and reliable instrument, was applied to a sample of 450 students of the initial level. The research found differences between the levels of neuropsychological maturity in pre-school children before and after the application of the program. In this sense, it should be pointed out that before the application of the program, 13.1% were at the beginning level, 72.2% were in process and 14.7% were at the achieved level; after the application of the program, 6.2% of the children were at the beginning level, 72.2% were in process and 21.6% were at the achieved level, which means that the children were at the beginning level, 72.2% were in process and 21.6% were at the achieved level. Therefore, it was concluded that the program generates a positive effect on psychomotor skills in preschool children, since highly significant differences were evidenced (z=-16.065; p<0.000).